Hospital Related Stress Among Patients Admitted to a Psychiatric In-patient Unit in India - Latha KS; Ravi Shankar BG (Online Journal of Health & Allied Sciences, 2011)
The psychiatric patient’s attitudes towards hospitalization have found an association between patient perceptions of the ward atmosphere and dissatisfaction. The aim of the study was to determine the aspects of stress related to hospitalization in inpatients admitted to a psychiatric facility. Fifty in-patients of both sexes admitted consecutively to a psychiatric unit in a General Hospital were asked to rate the importance of, and their satisfaction with, 38 different aspects of in-patient care and treatment. Results showed that the major sources of stress were related to having a violent patient near to his/her bed; being away from family; having to stay in closed wards; having to eat cold and tasteless food; losing income or job due to illness, being hospitalized away from home; not able to understand the jargons used by the clinical staff and not getting medication for sleep. A well-differentiated assessment of stress and satisfaction has implications for the evaluation of the quality of psychiatric care and for the improvement of in-patient psychiatric care.